The effect of tacrolimus conversion from immediate- to extended-release formulation on renal function in renal transplant patients: a meta-analysis - Chao, Sheng; Jia, Lei; Zhu, Kejing; Chen, Luobei; Niu, Yulin (Frontiers in Pharmacology, 2023)
Objective: Tacrolimus formulation affects the outcomes of a renal transplant, while the effect of its immediate- to extended-release conversion remains controversial. This meta-analysis aimed to compare the renal function before and after tacrolimus immediate- to extended-release conversion in renal transplant patients. Methods: PubMed, Cochrane, Embase, CNKI, CQVIP, and Wanfang databases were searched for articles regarding the effect of tacrolimus conversion from immediate- to extended-release formulation on renal function in renal transplant patients. The data on serum creatinine (Scr) or the estimated glomerular filtration rate (eGFR) before and after conversion were extracted and analyzed. Results: Ten studies with 743 renal transplant patients were included. Scr was reduced after conversion versus before conversion [mean difference (MD) (95% confidence interval (CI)): -8.00 (−14.33; −1.66) μmol/L, p = 0.01]. However, eGFR only showed an increased trend after conversion versus before conversion (MD (95% CI): 2.21 (−1.62, 6.03) mL/min/1.73 m2, p = 0.26) but without statistical significance. Furthermore, in patients with a follow-up duration ≥48 weeks, Scr was decreased after conversion versus before conversion (p = 0.005), but eGFR remained unchanged (p = 0.68). However, in patients with a follow-up duration <48 weeks, both Scr (p = 0.36) and eGFR (p = 0.24) were not different before conversion versus after conversion. Moreover, publication bias risk was low, and robustness assessed by sensitivity analysis was generally good. Conclusion: This meta-analysis favors studies indicating that the conversion of tacrolimus from an immediate-release to an extended-release formulation could improve the kidney function to some extent in renal transplant patients, and this advancement may be related to the administration period.